Diet of the Sanderlings (Calidris alba) at Punta Norte, Peninsula Valdés, Argentina - Hernández, Mailén Agostina (2005)
We describe the diet and food resource available to Sanderlings Calidris alba at Punta Norte, Península Valdés, Argentina. Fourteen potencial prey-types were identified of which the most abundant was the southern mussel Perumytilus purpuratus, followed by clams Lasaea sp. and different kinds of crustacean: stomatopods, the isopod Exosphaeroma sp. and several amphipod spp. However, despite their abundance, none of the molluscs were taken by Sanderling. Seventy Sanderling droppings were analyzed. These contained remains of five prey species: the isopod Exosphaeroma sp. (in 49% of droppings), several unidentified amphipod spp. (39%), the crab Cyrtograpsus affinis (31%), the polychaete Laeonereis acuta (13%), and various unidentified insects (1.5%). The droppings contained a mean of 1.6 individual of Exosphaeroma sp. With an average length of 6.1 mm (range: 5.0-8.1 mm). This diet is similar in terms of the taxonomic groups included to that recorded for Sanderling at other stop-over sites. When the diet is compared with the food on offer, it appears that the main components are highly mobile prey consistent with the Sanderling´s usual strategy of visual prey detection.